Status of Parthenium hysterophorus L. and its Biocontrol Agent, Zygogramma bicolorata Pallister in Uttarakhand - Dhiman, S. C.; Agarwal, Reshu (Indian Forester, 2010)
Parthenium hysterophorus L. is a weed that was imported into India along with the PL- 480 Mexican wheat seeds in the 50’s. The weed has since then spread into uncontrollable proportions invading million of ha of uncultivated wastelands, roadsides, railway lines forest lands and also invading large forest areas, agricultural and baren land, in different parts of Uttarakhand. Zygogramma bicolorata pallister, a potential biocontrol agent of this weed is also reaching to these places slowly. It has been recorded from all the places duing summer and rainy months (April to September). Larvae and adults of this beetle are voracious feeder and defoliate the weed leaving behind only stub of the plant.